Transcriptome Surveys in Silverfish Suggest a Multistep Origin of the Insect Odorant Receptor Gene Family - Thoma, Michael; Missbach, Christine; Jordan, Melissa D.; Grosse-Wilde, Ewald; Newcomb, Richard D.; Hansson, Bill S. (Frontiers in Ecology and Evolution, 2019)
The insect odorant receptor (Or) gene family is among the largest multigene families in insect genomes, but its evolutionary origin and mode of expansion is still a matter of debate. We performed transcriptomic surveys of two wingless insect species, the silverfish Lepisma saccharina and Tricholepidion gertschi, and identified multiple Or gene family members in both species. A phylogenetic analysis suggests that the silverfish Ors do not fall into the clade comprised of more derived flying insect ligand-binding Ors, but, along with bristletail, firebrat and some mayfly Ors, are consistently resolved as a distinct set of genes that may constitute an evolutionary intermediate between gustatory receptors and the more derived Ors of flying insects. We propose to consider these “primitive Ors” separately from higher insect Ors until their cellular expression patterns and function are resolved and suggest a multistep evolutionary scenario ultimately leading to the highly sensitive, rapidly evolving and physiologically diverse Or gene family observed in higher insects.